MONTENEGRO SKIN TEST AND AGE OF SKIN LESION AS PREDICTORS OF TREATMENT FAILURE IN CUTANEOUS LEISHMANIASIS - Liliane de Fátima Antonio; Aline Fagundes; Raquel Vasconcellos Carvalhaes Oliveira; Priscila Garcia Pinto; Sandro Javier Bedoya-Pacheco; Érica de Camargo Ferreira e Vasconcellos; Maria Cláudia Valete-Rosalino; Marcelo Rosandiski Lyra; Sônia Regina Lambert Passos; Maria Inês Fernandes Pimentel; Armando de Oliveira Schubach (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
A case-control study was conducted to examine the association among the Montenegro skin test (MST), age of skin lesion and therapeutic response in patients with cutaneous leishmaniasis (CL) treated at Evandro Chagas National Institute of Infectious Diseases (INI), Oswaldo Cruz Foundation (FIOCRUZ), Rio de Janeiro, Brazil. For each treatment failure (case), two controls showing skin lesion healing following treatment, paired by sex and age, were randomly selected. All patients were treated with 5 mg Sb5+/kg/day of intramuscular meglumine antimoniate (Sb5+) for 30 successive days. Patients with CL were approximately five times more likely to fail when lesions were less than two months old at the first appointment. Patients with treatment failure showed less intense MST reactions than patients progressing to clinical cure. For each 10 mm of increase in MST response, there was a 26% reduction in the chance of treatment failure. An early treatment - defined as a treatment applied for skin lesions, which starts when they are less than two months old at the first appointment -, as well as a poor cellular immune response, reflected by lower reactivity in MST, were associated with treatment failure in cutaneous leishmaniasis.